The dark side of mental toughness: a meta-analysis of the relationship between the dark triad traits and mental toughness - Liang, Taihe; Wang, Xianfei; Ng, Sanfan; Xu, Xuefeng; Ning, Ziheng (Frontiers in Psychology, 2024)
This meta-analysis investigates the relationships between the Dark Triad personality traits (narcissism, Machiavellianism, and psychopathy) and mental toughness. A comprehensive literature search was conducted, yielding 27 effect sizes with a total of 12,378 participants. The results revealed a significant moderate positive association between narcissism and mental toughness (r = 0.327, p < 0.001), suggesting that individuals with higher levels of narcissism tend to exhibit greater mental toughness.However, no significant associations were found between Machiavellianism (r = 0.023, p = 0.719) or psychopathy (r = -0.022, p = 0.625) and mental toughness. The findings contribute to a more nuanced understanding of the Dark Triad traits and their differential associations with positive psychological constructs, highlighting the unique role of narcissism in mental toughness. This meta-analysis provides valuable insights for future research and practical applications in fostering adaptive aspects of narcissism while mitigating its potential negative consequences.